2008
DOI: 10.4028/www.scientific.net/kem.381-382.241
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Surface Material Measures for Areal Surface Texture Measuring Instruments: Measuring Conditions for the Areal Profiling

Abstract: This paper describes the software gauge data for surface texture standard using the non-causal 2D auto-regressive model (A-R model). This model can provide with 3D irregular surface topography and intentional geometrical characteristics from specified surface texture parameters. The measurement area consists of a periodical combination of the generated sampling area data. The surface roughness parameters introduced from the gauge data on a defined evaluation area can be insensitive to size and location of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…We proposed a calculation algorithm to generate random surface topography data using a non-causal 2D auto-regressive (2D AR) model. In this study the boundary conditions for four sides were modified so that exactly one cycle height data or unit areal data can be introduced [4]. This means that height data on both sides are identical to each other.…”
Section: Generation Of Irregular Surface Topography Datamentioning
confidence: 99%
See 2 more Smart Citations
“…We proposed a calculation algorithm to generate random surface topography data using a non-causal 2D auto-regressive (2D AR) model. In this study the boundary conditions for four sides were modified so that exactly one cycle height data or unit areal data can be introduced [4]. This means that height data on both sides are identical to each other.…”
Section: Generation Of Irregular Surface Topography Datamentioning
confidence: 99%
“…As mentioned above, the sampling distances dx and dy for 3D surface texture measurement in this study were determined as shown in table 7. The evaluation area was defined as 770 μm (x) × 770 μm (y) [4]. If it measures on this condition, even if the difference of the value of Sz compares with the result of dx = dy = 0.5 μm, it will become below 3% (0.2 μm).…”
Section: Measuring Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Time series and FFTs are popular in generating 3D surfaces. Time series models were used by Whitehouse 17 , Gu and Huang, 18 Hong and Ehmann, 19 Uchidate et al, 20 Nemoto et al, 21 and Uchidate et al 22…”
Section: Introductionmentioning
confidence: 99%
“…Time series and FFTs are popular in generating 3D surfaces. Time series models were used by Whitehouse 17 , Gu and Huang, 18 Hong and Ehmann, 19 Uchidate et al, 20 Nemoto et al, 21 and Uchidate et al 22 Usually, after application of time series models, only a few points near the origin of the autocorrelation function can be properly simulated. In order to cope with the storage space and time limitations of the mentioned methods a FFT application was proposed.…”
Section: Introductionmentioning
confidence: 99%